The Fookien Times Philippines yearbook, decennial index, 1981-1990 - Mata, Maria Nena R. (Manila Fookien Times Yearbook Pub., 1991)
This decennial index presents comprehensive and full indexing of the year 1981 thru 1990 issues of the Fookien Times Philippines yearbook as compared to the 1983 Master Index (covering the period 1936 to 1980, with some missing issues). It includes the alphabetical listing of the country's top business concerns, which advertised in the covered years. It features the biographical sketches of personages in the government sector, in private enterprises, as well as the members of the diplomatic corps, both foreign and local.
Keywords: Philippines -- Yearbooks -- Indexes